The Paracrine Feedback Loop Between Vitamin D3 (1, 25(OH)2D3) and PTHrP in Prehypertrophic Chondrocytes. Issue 12 (December 2014) - Bach, Frances C.; Rutten, Kirsten; Hendriks, Kristyanne; Riemers, Frank M.; Cornelissen, Peter; de Bruin, Alain; Arkesteijn, Ger J.; Wubbolts, Richard; Horton, William A.; Penning, Louis C.; Tryfonidou, Marianna A.
<x xml:space="preserve">Abstract</x> The endocrine feedback loop between vitamin D3 (1, 25(OH)2D3) and parathyroid hormone (PTH) plays a central role in skeletal development. PTH‐related protein (PTHrP) shares homology and its receptor (PTHR1) with PTH. The aim of this study was to investigate whether there is a functional paracrine feedback loop between 1, 25(OH)2D3 and PTHrP in the growth plate, in parallel with the endocrine feedback loop between 1, 25(OH)2D3 and PTH. This was investigated in ATDC5 cells treated with 10−8 M 1, 25(OH)2D3 or PTHrP, Col2‐pd2EGFP transgenic mice, and primary Col2‐pd2EGFP growth plate chondrocytes isolated by FACS, using RT‐qPCR, Western blot, PTHrP ELISA, chromatin immunoprecipitation (ChIP) assay, silencing of the 1, 25(OH)2D3 receptor (VDR), immunofluorescent staining, immunohistochemistry, and histomorphometric analysis of the growth plate. The ChIP assay confirmed functional binding of the VDR to the PTHrP promoter, but not to the PTHR1 promoter. Treatment with 1, 25(OH)2D3 decreased PTHrP protein production, an effect which was prevented by silencing of the VDR. Treatment with PTHrP significantly induced VDR production, but did not affect 1α‐ and 24‐hydroxylase expression. Hypertrophic differentiation was inhibited by PTHrP and 1, 25(OH)2D3 treatment. Taken together, these findings indicate that there is a functional paracrine feedback loop between 1, 25(OH)2D3 and PTHrP in the growth plate. 1, 25(OH)2D3 decreases PTHrP production, while PTHrP increases chondrocyte sensitivity to 1, 25(OH)2D3 by increasing VDR production. In light of the role of 1, 25(OH)2D3 and PTHrP in modulating chondrocyte differentiation, 1, 25(OH)2D3 in addition to PTHrP could potentially be used to prevent undesirable hypertrophic chondrocyte differentiation during cartilage repair or regeneration. J. Cell. Physiol. 229: 1999–2014, 2014. © 2014 Wiley Periodicals, Inc.